PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN PEMAHAMAN KARIR SISWA KELAS XI MIPA SMA HANDAYANI PEKANBARU TAHUN AJARAN 2014/2015 - Nur Rahmi Nur Rahmi; Raja Erlizon Raja Erlizon; Tri Umari Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to; 1) to identify the increasing career of student after taken service group guidance, 2) to identify the process of information services to the students’ carrier understanding, 3) to identify the progress of career understanding after service group guidance being given, 4) to identify the differences between before and after service group guidance being given to the students career understanding, 5) to identify the increasing of student career understanding after service group guidance were carried out. The subject of this research were students from class XI Science SMA Handayani Pekanbaru, with 90 respondents. The sample was 30% of the population, the sample was determined by using simple random sampling technique. Based on the results of data before given service group guidance, it was found that 7% on high category, 33 % on medium level and 60% on low level category. However, the result after getting service group guidance showed that 37 % on High level category, 50 % on medium and 13 % on low category. Based on the hypothesis result, there are significant influences of service group guidance to the students self adjustment, that is 25 %.Keywords: Group Counseling and career understanding